A New Genotype-Phenotype Genetic Algorithm for the Two-Dimensional Strip Packing Problem with Rotation of 90° [Un Nuevo Algoritmo Genético de Genotipo-Fenotipo Para el Problema de Strip Packing de Dos Dimensiones Con Rotación de 90°] - Contreras-Bolton, C (Pontificia Universidad Javeriana, 2016)
Given a set of rectangular pieces and a fixed width with infinite length, the strip-packing problem (SPP) of two dimensions (2D), with a rotation of pieces in 90° consists of orthogonally placing all the pieces on the strip, without overlapping them, minimizing the height of the strip used. Several algorithms have been proposed to solve this problem, being Genetic Algorithms one of the most popular approach due to it effectiveness solving NP-Hard problems. In this paper, three binary representations, and classic crossover and mutation operators are introduced. A comparison of the three binary representations on a subset of benchmarking instances is performed. The representation R2 outperforms the results obtained by representation R1 and R3. Indeed, some of the bestknown results found by previous published approaches are improved. © 2015, Pontificia Universidad Javeriana. All rights reserved.